Synthesis, structural and chemosensitivity studies of arene d6 metal complexes having N‐phenyl‐N´‐(pyridyl/pyrimidyl)thiourea derivatives - Adhikari, Sanjay; Hussain, Omar; Phillips, Roger M.; Kaminsky, Werner; Kollipara, Mohan Rao (Applied organometallic chemistry, 2018)
The d6 metal complexes of thiourea derivatives were synthesized to investigate its cytotoxicity. Treatment of various N‐phenyl‐N´ pyridyl/pyrimidyl thiourea ligands with half‐sandwich d6 metal precursors yielded a series of cationic complexes. Reactions of ligand (L1‐L3) with [(p‐cymene)RuCl2]2 and [Cp*MCl2]2 (M = Rh/Ir) led to the formation of a series of cationic complexes bearing general formula [(arene)M(L1)к2(N,S)Cl]+, [(arene)M(L2)к2(N,S)Cl]+ and [(arene)M(L3)к2(N,S)Cl]+ [arene = p‐cymene, M = Ru (1, 4, 7); Cp*, M = Rh (2, 5, 8); Cp*, Ir (3, 6, 9)]. These compounds were isolated as their chloride salts. X‐ray crystallographic studies of the complexes revealed the coordination of the ligands to the metal in a bidentate chelating N,S‐ manner. Further the cytotoxicity studies of the thiourea derivatives and its complexes evaluated against HCT‐116 (human colorectal cancer), MIA‐PaCa‐2 (human pancreatic cancer) and ARPE‐19 (non‐cancer retinal epithelium) cancer cell lines showed that the thiourea ligands displayed no activity. Upon complexation however, the metal compounds possesses cytotoxicity and whilst potency is less than cisplatin, several complexes exhibited greater selectivity for HCT‐116 or MIA‐PaCa‐2 cells compared to ARPE‐19 cells than cisplatin in vitro. Rhodium complexes of thiourea derivatives were found to be more potent as compared to ruthenium and iridium complexes. Reaction of arene d6 metal complexes with thiourea derivatives afforded series of mononuclear compounds. The thiourea derivatives are not cytotoxic however after complexation they are cytotoxic.